EFFICIENCY OF COMPUTER TESTING IN INFORMATIZATION OF EDUCATIONAL PROCESS IN MEDICAL SCHOOL - N V Boldina; G S Mal; O V Polyakova; S N Udalova; G V Novikova (RUDN Journal of Informatization in Education, 2016)
Informatization of educational process of training students of medical school is described in the article. Methodical aspects of computer testing of students 3 courses of medical faculty of 2013-2016 studying at department of pharmacology of the Kursk state medical university which give the chance to reveal the level of assimilation of a training material by students are stated. The attention to the most important problem of the current control - stimulation of regular and purposeful work of students is paid.